Hierarchical NiCo-LDH/NiCoP@NiMn-LDH hybrid electrodes on carbon cloth for excellent supercapacitors. Issue 31 (27th July 2018) - Liang, Haoyan; Lin, Jinghuang; Jia, Henan; Chen, Shulin; Qi, Junlei; Cao, Jian; Lin, Tiesong; Fei, Weidong; Feng, Jicai
Abstract : To realize high-performance and long life span supercapacitors, highly electrochemically active materials and rational design of structure are highly desirable. Abstract : To realize high-performance and long life span supercapacitors, highly electrochemically active materials and rational design of structure are highly desirable. Herein, a hierarchical NiCo-LDH/NiCoP@NiMn-LDH hybrid electrode (NCLP@NiMn-LDH) was synthesized on carbon cloth via a hydrothermal reaction and phosphorization treatment. Owing to the introduction of NiCoP and design of the core–shell structure, the hybrid electrode showed significantly improved electrochemical performance. The as-fabricated hybrid electrode exhibited a high specific capacitance of 2318 F g −1 at 1 A g −1, with a superior cyclic stability. Additionally, an asymmetric supercapacitor (NCLP@NiMn-LDH//AC) was assembled with a voltage window of 1.5 V. The ASC device delivered a maximum energy density of 42.2 W h kg −1 at a power density of 750 W kg −1 .